Safety, efficacy and drug survival of biologics and biosimilars for moderate‐to‐severe plaque psoriasis. (9th January 2018) - Egeberg, A.; Ottosen, M.B.; Gniadecki, R.; Broesby‐Olsen, S.; Dam, T.N.; Bryld, L.E.; Rasmussen, M.K.; Skov, L.
Summary: Background: Real‐life data on newer biological and biosimilar agents for moderate‐to‐severe psoriasis are lacking. Objectives: To examine safety, efficacy and time to discontinuation (drug survival) of biologics (adalimumab, etanercept, infliximab, secukinumab and ustekinumab) and compare originators with biosimilars (i.e. Enbrel with Benepali, and Remicade with Remsima). Methods: The DERMBIO registry contains data on all Danish patients with moderate‐to‐severe plaque psoriasis treated with biologics. We examined patients treated between 1 January 2007 and 31 March 2017. We used Kaplan–Meier survival curves and Cox regression to examine drug survival patterns. Results: A total of 3495 treatment series (2161 patients) were included (adalimumab n  =   1332; etanercept n  =   579; infliximab n  =   333; ustekinumab n  =   1055 and secukinumab n  =   196). Secukinumab had the highest number of PASI 100 (100% improvement from baseline Psoriasis Area and Severity Index) respondents, but also the lowest drug survival among all the biologics. Ustekinumab had the highest drug survival overall. There were no significant differences in discontinuation risk between originator and biosimilar versions of infliximab or etanercept. Treatment with higher than approved dosages was frequent for all drugs except for adalimumab and secukinumab. Adverse events (predominantly infections) were most frequent for secukinumab compared with the other agents. Conclusions: Ustekinumab was associated with the highest drug survival, and secukinumab with the lowest, although most patients on secukinumab were non‐naïve. Switching from originator to biosimilar had no significant impact on drug survival, and the safety profiles were comparable. Adverse events occurred most frequently with secukinumab. Future studies are warranted to assess the long‐term safety of novel biologics for psoriasis. Abstract : What's already known about this topic? Previous studies have reported that long‐term drug survival is dependent on the patient's sex, choice of drug and previous exposure to biologics. Ustekinumab has been put forward as the biologic with the highest drug survival. What does this study add? Ustekinumab had higher drug survival than secukinumab, adalimumab, infliximab and etanercept. Secukinumab appeared to have the lowest drug survival and highest risk of adverse events. Results were comparable between originators and biosimilars. These findings may affect choice of therapy for candidates for biological therapy, including both bio‐naïve and currently well treated patients who are currently, as well as those who have failed on one or more biological agents. Linked Comment:  Vender. Br J Dermatol 2018;178 :328–329 . Plain language summary available online Respond to this article